2018
DOI: 10.1007/978-1-4939-7698-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Blood-Testis Barrier (BTB) Dynamics, Role of Actin-, and Microtubule-Based Cytoskeletons

Abstract: The blood-testis barrier (BTB) is an important ultrastructure in the testis that supports meiosis and postmeiotic spermatid development since a delay in the establishment of a functional Sertoli cell barrier during postnatal development in rats or mice by 17–20 day postpartum (dpp) would lead to a delay of the first wave of meiosis. Furthermore, irreversible disruption of the BTB by toxicants also induces infertility in rodents. Herein, we summarize recent findings that BTB dynamics (i.e., disassembly, reassem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…Therefore, the morphological changes that Sertoli cells undergo as part of their maturation process reflect the changes that germ cells in direct contact with them undergo as well. A key player in this mutual maturation process is the Sertoli cell cytoskeleton, mainly formed by microtubules, actin filaments and vimentin intermediate filaments [23,24,25,26,27].…”
Section: Sertoli Cell Maturation During Postnatal Developmentmentioning
confidence: 99%
“…Therefore, the morphological changes that Sertoli cells undergo as part of their maturation process reflect the changes that germ cells in direct contact with them undergo as well. A key player in this mutual maturation process is the Sertoli cell cytoskeleton, mainly formed by microtubules, actin filaments and vimentin intermediate filaments [23,24,25,26,27].…”
Section: Sertoli Cell Maturation During Postnatal Developmentmentioning
confidence: 99%
“…In fact, by analysing the subcellular localization and integrity of the main components of cell cytoskeleton, namely F-Actin fibres, Vimentin-based intermediate filaments and α-tubulin microtubules, we observed that the development of a C. trachomatis inclusion into a human Sertoli cell led to alteration in its cytoskeleton. Recent studies have shown that actin and microtubule-based cytoskeleton in Sertoli cells plays a crucial role to preserve the homeostasis of the BTB 20 . Our observation that Vimentin-based intermediate filaments and α-tubulin microtubules were re-organized in thick fibres surrounding the chlamydial inclusion, hints at the intriguing possibility that C. trachomatis might adversely affect the integrity of the BTB, and, hence, impair the spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To accommodate the entry of spermatocytes into the adluminal compartment, existing junctions above them must transiently disassemble, leading to changes in protein-protein interactions 17 . The restructuring of the BTB is a complex process that is mainly supported by the Sertoli cell cytoskeleton, and, as such, the maintenance of its structural integrity is essential for the generation of mature functional spermatozoa 17,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…ES includes basal ES at the Sertoli cell-cell interface of the BTB, and the apical ES at the Sertoli-spermatid interface (Li et al, 2015). Actin-based cytoskeletons in Sertoli and germ cells play crucial roles in the regulation of homeostasis of the BTB and the cytoskeletal elements at the basal ES (Wen et al, 2018c). Even though there have been many recent reports that have highlighted the factors involved in the regulation of the BTB and ES (Wen et al, 2018;Li et al, 2015), the intriguing cross-talk mechanism(s) between basal and apical ES are still not fully understood, because the restructuring of the BTB close to the basement membrane and the disruption of the apical tubulobulbar complex (TBC) at the luminal edge of the epithelium happen almost concurrently (Li et al, 2015).…”
Section: Esmentioning
confidence: 99%